A spectrally overlaid flexible bandwidth utilisation scheme for cellular CDMA systems. (7th December 2006) - Sivaradje, G.; Dananjayan, P.
Future wireless communication systems need to utilise bandwidth with improved efficiency in order to manage the evergrowing traffic conditions. The capacity of a link can be improved by spectrally overlaying narrowband subsystems over a single wideband system. A micro/macro cellular CDMA overlay system was considered in the present study. Important issues such as the interference, the desired user signal power in the reverse link, the system parameters affecting the reverse link capacity, the spectral overlay ratio and distance between micro and macrocells base stations were analysed. The relative power used, the interference obtained due to the cousers and maximum total throughput in a particular cell have been evaluated. A real time simulation of a CDMA system in a cellular environment consisting of several narrowbands overlaid on a wideband system clearly shows that capacity enhancement can be achieved due to the overlay of narrowband and wideband CDMA systems.